Pyrenees as the southernmost European refugium of glacial relict land snails - Horsák, Michal; Jiménez-Alfaro, Borja; Pladevall-Izard, Eulàlia; Pérez-Haase, Aaron; Kafimola, Sara; Horsáková, Veronika (Scientific reports, 2025)
Biogeographical relicts, particularly glacial relicts, are species that have survived postglacial climatic shifts in isolated refugia. In temperate Europe, such species are commonly found in high-altitude mountain ranges, including the Alps, Carpathians, and Pyrenees. While glacial relict land snails are well-documented in the Alps and Carpathians, their occurrence in the Pyrenees remains largely unexplored. In this study, we report the first records of Columella columella in the Iberian Peninsula, found in alpine rocky tundra and alkaline spring fen habitats, far south of its known distribution. Additionally, we report the first presence of Pyramidula saxatilis in Spain, a rock-dwelling species with a distinct Pyrenean haplotype, suggesting its long-term isolation. Our findings also challenge previous records of Vertigo genesii in the Pyrenees, which seem to represent Vertigo hoppii (syn. V. arctica). Furthermore, we document Vertigo alpestris for the first time in Spain, revealing a unique haplotype shared with an Icelandic population. These findings highlight the Pyrenees as a potential southern refugium for glacial relict snails and emphasize the need for further research and conservation measures to protect these highly isolated populations from habitat degradation, particularly due to overgrazing.
Keywords: Disjunct occurrence; Snails; ekosystém; Europe; Glacial relict; Gastropoda; Evropa; Haplotypes; Distribution; ledový příkrov; Španělsko; Ice Cover; hlemýždi; Refugium; zvířata; Spain; fylogeneze; haplotypy; Genetic sequences; Ecosystem; Phylogeny; refugium; Animals